An efficient piezoelectric energy harvester with frequency self-tuning. (26th May 2017) - Cheng, Yukun; Wu, Nan; Wang, Quan
Abstract: A beam energy harvester made of an aluminum substrate surface bonded with piezoelectric patches and a stack actuator is developed to achieve an efficient energy harvesting technology with a new developed frequency self-tuning process. To accomplish the self-tuning process, an adjustable axial force applied to the energy harvester is generated by the piezoelectric stack actuator. The stack actuator is controlled by a charged voltage on a small tuning capacitor, which is connected to and charged by the harvester. The function of the stack actuator is to automatically tune the natural frequency of the harvester to match the major exciting frequency of the ambient vibration through the tuning capacitor. To describe the energy harvesting and the self-tuning process, an iteration numerical method is developed to solve the dynamic response of the harvester and the generated electric charge. Effects of the piezoelectric patch sizes on the energy harvester's power generation are conducted and discussed. Research findings show that the self-tuning process significantly increases the power output from the harvester by more than 26 times compared to the one without the developed tuning process. Furthermore, the finite element method (FEM) is employed to verify the effectiveness of the proposed self-tuning method.